Building popular support for post-conflict constitutions: Lessons from Nepal - Kyle, Jordan; Resnick, Danielle (Brookings Institution, 2023)
In early 2023, the United Nations announced that the world is facing the highest number of violent conflicts since World War II, with a majority of these being civil conflicts. Historically, ending civil conflict and fostering democratic transitions has involved constitutional reforms that address the grievances that originally sparked violence. In fact, over 100 peace agreements signed between 1989 and 2020 have included provisions for constitutional reform. However, the period of negotiating constitutional reforms is particularly precarious in such settings and can lead to further destabilization if too many groups’ expectations are not met.